2016
DOI: 10.1002/polb.24266
|View full text |Cite
|
Sign up to set email alerts
|

Odd‐even effect during layer‐by‐layer assembly of polyelectrolytes inspired by marine mussel

Abstract: Biomimetic polyelectrolyte of Dopa modified poly(acrylic acid) (PAADopa) was synthesized taking advantage of Dopa, the major unit of marine adhesive proteins. Zinc crosslinked PAADopa (PAADopa‐Zn) were formed at acidic pH for more compact structure and assembled with the positively charged polyethylenimine (PEI) to build robust polyelectrolyte multilayers at high salt concentration. Effects of pH, crosslinking degree, and salt concentration on polymer structure, film building process, and morphology were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The PDADMAC terminated PEM ( Figure 7 a, BL) swells more strongly because of a higher concentration of counter ions [ 43 ] and therefore a higher osmotic pressure in the PEM [ 25 , 44 ]. This dependency of the water uptake on the outermost PE layer is commonly observed for PEMs and known as the odd-even effect [ 32 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 95%
“…The PDADMAC terminated PEM ( Figure 7 a, BL) swells more strongly because of a higher concentration of counter ions [ 43 ] and therefore a higher osmotic pressure in the PEM [ 25 , 44 ]. This dependency of the water uptake on the outermost PE layer is commonly observed for PEMs and known as the odd-even effect [ 32 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 95%
“…Surface charge inversion after every deposition step is an essential precondition for PEM formation . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The building blocks of PEMs can range from small organic molecules to inorganic compounds and macromolecules including polysaccharides, proteins, viruses, DNA and various kinds of nanoparticles, showing a possible way for surface engineering to achieve desired properties . This ecofriendly technique can be enabled to control film structure and properties to realize successful PEM construction with tunable behaviors . Polyelectrolyte thin film layers obtained by LbL deposition are continuously studied due to their potential applications in various technologies, and interesting fundamental questions arise from their complex nature .…”
Section: Introductionmentioning
confidence: 99%
“…The favourable adhesive properties exuded by mussels (the most common organism researched for underwater adhesion) have been extensively explored in numerous reviews [ 123 , 124 , 125 ], where 3,4-dihydroxy-phenylalanine (DOPA) moieties are considered the primary source of mussel adhesion in their natural environment. To exploit this property, a DOPA-modified PAA layer crosslinked with zinc was incorporated as the polyanionic component alongside a positively charged PEI layer to determine the effects of LBL assembly of PEs [ 126 ]. The multilayered system was comparative to the bioactive C-CHT system.…”
Section: Fabrication Of Different Types Of Pe Gelsmentioning
confidence: 99%
“…In contrast, a more compact structure was obtained for an adhesive polyanionic layer dominated by a more crosslinked structure, preventing the absorption of the surrounding liquid environment. Thus, an odd-numbered multilayer presents a more hydrophilic nature with a loosely packed structure, thereby negatively impacting the overall parameters such as thickness, swelling and adhesion [ 126 ]. DOPA moieties have further shown their advantages in obtaining excellent underwater adhesion, where Jiao et al [ 95 ] demonstrated how their polyelectrolytic system could withstand ~200 min of ultrasonication with only a negligible change.…”
Section: Fabrication Of Different Types Of Pe Gelsmentioning
confidence: 99%